2012
DOI: 10.1016/j.febslet.2012.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Dermokine‐β impairs ERK signaling through direct binding to GRP78

Abstract: a b s t r a c tDermokine-b is abundant in stratified epithelia and in differentiating cultured keratinocytes. In this study, we investigated the role of dermokine-b in differentiation of keratinocytes. Treatment of keratinocytes or skin tumor cells with dermokine-b attenuated phosphorylation of extracellularsignal-regulated kinase (ERK). Exposure of cells to dermokine-b, as well as its carboxyl-terminus domain peptide, interrupted phosphorylation of ERK and stimulated dermokine gene expression. Inhibition of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…According to recently published data concerning overexpression of DMKN b in human keratinocytes, the absence of Dmkn b would be expected to lead to an increase in Erk phosphorylation resulting in a decrease in Dmkn and Ivl gene expression (Higashi et al, 2012). By contrast, our results show no difference in the balance between Erk and phosphorylated Erk in the skin of KO compared to control mice.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…According to recently published data concerning overexpression of DMKN b in human keratinocytes, the absence of Dmkn b would be expected to lead to an increase in Erk phosphorylation resulting in a decrease in Dmkn and Ivl gene expression (Higashi et al, 2012). By contrast, our results show no difference in the balance between Erk and phosphorylated Erk in the skin of KO compared to control mice.…”
Section: Discussionsupporting
confidence: 55%
“…3C). It has previously been shown that DMKN b decreases the phosphorylation of ERK1/2 and subsequently increases caspase activity in cultured human keratinocytes (Higashi et al, 2012). Our analysis of the phosphorylation level of ERK1/2 by immunoblotting ( Fig.…”
Section: Expression Of Murine Dmkn During Cutaneous Wound Healingmentioning
confidence: 56%
See 1 more Smart Citation
“…Expressions of human GALNT1 and LARGE were quantified using MESA Blue qPCR Mastermix (Eurogentec, Seraing, Belgium) as previously described (14). The PCR primers used were as follows: GALNT1 forward, 5Ј-ATGACCTATG-GTGGGTTCAACT-3Ј and reverse, 5Ј-CTGACAGGAAGAG-TCCGATCA-3Ј; LARGE forward, 5Ј-TCCGAGCAGTGCTAC-AGAGA-3Ј and reverse, 5Ј-TTGCGAAAAAACTCCACATG-3Ј.…”
Section: Dna Microarray Analysis and Real Time Rt-pcr Assay-mentioning
confidence: 99%
“…Moreover, recombinant DMKN inhibited ERK phosphorylation in cultured keratinocytes and delayed wound closure in mice (75,76). However, the mechanisms of DMKN activity in keratinocyte differentiation and inflammatory skin diseases remain to be determined.…”
Section: Discussionmentioning
confidence: 99%